THE ANALISIS MAQASID AL-SHARI’AH (HIFDL AQL & HIFDL MAL) TENTANG TINGKAT KESEJAHTERAAN PERAJIN BATIK BERBASIS KEMITRAAN UMKM DI TANJUNGBUMI BANGKALAN - Akhiruddin, Syahrul; Nasik, Khoirun (Qawwam : The Leader's Writing, 2023)
The batik craft sector in Bangkalan occupies the region's first leading potential. More than five sub districts are centers that produce a lot of batik. This sector is expected to be able to support and accelerate economic growth to eradicate poverty. Tanjungbumi is one of the centers of batik, starting from the wives who divert their anxiety with batik activities because they are waiting for their husbands to go to sea. Meanwhile, the basic philosophy of the Madurese which is Islam considers batik work as an opportunity to work. Their philosophy of life considers batik as an opportunity to work. Besides developing as a work of art, batik is also a promising industry. The potential of batik is so great to be developed. This research is structured using qualitative research methods, namely observing people in their environment, interacting with them, trying to understand their language and interpretation of the world around them with the aim of gaining understanding and understanding of an event or human behavior in an organization or institution. Sources of data used in this study using primary and secondary data sources, most batik artisans are women who are more tenacious and patient in doing a job, moreover the process of making batik takes a long time, it can take weeks or even years. Of course the process requires a lot of intervention starting from fabric making, basic batik painting, motif drawing, painting, color locking and other processes. One step is carried out by one person and the cost varies depending on the difficulty. Compared to civil servants, the salary is certainly higher, but the most important thing is to get blessings. Can meet daily needs, even still able to save. Of course, for children's school fees, even though they have not been able to go to college.